Saliva and plasma metabolome analysis during the five days before foaling in the mare - Lydie Nadal-Desbarats; Camille Dupuy; Frédéric Montigny; Priscila Silvana Bertevello; Cécile Douet; Amandine Gesbert; Fabrice Reigner; Ghylène Goudet (PLoS ONE, 2026)
Saliva is a relevant biofluid for real-time welfare-friendly monitoring of systemic events in animals, because some bioanalytes have a systemic origin and its collection is painless, stress-free and non-invasive. Our aim was to analyze the metabolome of equine saliva during the five days before foaling, with a focus on identifying metabolites whose level significantly changed before parturition, that could be potential salivary biomarkers of the onset of parturition. We compared the saliva and plasma metabolomes to investigate their relationship. Saliva and blood samples were collected from twelve mares once a day in the morning, from 322 days of gestation to the day of foaling. Samples collected from four days before the day of parturition (D-4) to the day when parturition occurred (D0) were analyzed by 1 H Nuclear Magnetic Resonance spectroscopy. We identified 50 metabolites in saliva and 51 in plasma. In saliva, the levels of three metabolites and three groups of metabolites showed significant differences between the days. In particular, acetic acid significantly decreased three days before D0 and again on D0, isovaleric acid significantly increased from four days before D0 to D0, and lactic acid significantly decreased between three and two days before D0. In plasma, the levels of D-Glucose and four groups of metabolites showed significant differences between the days. D-Glucose significantly increased between three and two days before D0, and again on D0. In conclusion, significant changes in the salivary metabolome have been shown in the antepartum period in the mare. However, only minor changes in the levels of these metabolites were observed, without any significant threshold that would allow the prediction of foaling. Significant modifications of the plasma level of glucose have been observed before foaling. The development of non-invasive glucose monitoring sensors could allow the development of non-invasive detection method for the prediction of foaling.